Qualidade fisiológica e sanitária de sementes de amendoim durante o processo de produção - Barbosa, Rafael Marani [UNESP] (2014)
The peanut seeds production of high physiological and sanitary quality requires careful handling. During the production process, the seeds are subject to stages that can interfere on their quality. The objective of this work was to verify the effect of the stages of production process on the physiological and sanitary quality of peanut seeds. In two experimental years, sampling after the digging and combining, carriage and drying were performed. After this stages, the pods were stored and sampled at two, four and six months. During processing, seeds were sampled after mechanical threshing, classification by size, density and color separation, and after chemical fungicide seed treatment. The water content, sanitary and physiological quality, by germination and vigor were evaluated. In the first year, from the digging to the end of storage, there was a high seed quality and processing reduced its quality. In the second year, the seeds from the steps of harvesting and storage for six months showed low quality. After processing, increase in the seeds performance was observed. During the production process, the mechanical threshing stage can reduce peanut seed quality. The different stages of the production process, when executed properly contribute to the improvement of the performance potential of peanut seeds